52.3k views
16 votes
Sue has 18 sweets.

Tony also has 18 sweets.
Sue gives Tony x sweets.
Sue then eats 5 of her sweets.
Tony then eats half of his sweets.
Write expressions for the number of sweets Sue and Tony now have.

User Porlicus
by
5.1k points

1 Answer

0 votes

Explanation:

Find out the expressions for the number of sweets sue and tony have now .

To proof

As given

Sue has 18 sweets. tony has 18 sweets.sue gives tony x sweets

thus

sue sweets = 18 - x

Tony sweets = 18 + x

As given

Sue then eats 5 sweets. Tony then eats half of his sweets

sue sweets becomes = 18 -5 -x

= 13 - x

Tony sweets become= 18 + x /2

= 9+ x/2

hence proved.

Hence proved

User Yuriy
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.